Emergence of pediatric melioidosis in Siem Reap, Cambodia. - Pagnarith, Y; Kumar, V; Thaipadungpanit, J; Wuthiekanun, V; Amornchai, P; Sin, L; Day, N; Peacock, S (2010)
We describe the first cases of pediatric melioidosis in Cambodia. Thirty-nine cases were diagnosed at the Angkor Hospital for Children, Siem Reap, between October 2005 and December 2008 after the introduction of microbiology capabilities. Median age was 7.8 years (range = 1.6-16.2 years), 15 cases were male (38%), and 4 cases had pre-existing conditions that may have pre-disposed the patient to melioidosis. Infection was localized in 27 cases (69%) and disseminated in 12 cases (31%). Eleven cases (28%) were treated as outpatients, and 28 (72%) cases were admitted. Eight children (21%) died a median of 2 days after admission; seven deaths were attributable to melioidosis, all of which occurred in children receiving suboptimal antimicrobial therapy and before bacteriological culture results were available. Our findings indicate the need for heightened awareness of melioidosis in Cambodia, and they have led us to review microbiology procedures and antimicrobial prescribing of suspected and confirmed cases.